An unusual case of intra-abdominal testicular torsion: Role of laparoscopy - Alfonso Papparella; Fabiano Nino; Sandra Coppola; Pio Parmeggiani (Wolters Kluwer Medknow Publications, 2013)
The authors report a case of intra-abdominal testicular torsion, where laparoscopy has been useful for diagnosis and surgical management. A boy was presented with a left impalpable testis. Laparoscopy revealed a twisted spermatic cord at the inlet pelvis, which ended in a testicular remnant located in the sub-umbilical area. After orchiectomy, the pathologist confirmed testicular atrophy. Diagnosis of intra-abdominal testicular torsion should be considered in patients with impalpable testis and abdominal pain, but could not be excluded in those with no symptoms.